The Hate/Love Dichotomy in Adib Kamaluddin’s Poetry: An Analytical Study - Muhammad Salih, Muhammad Jassim; Ajimi, Ibrahim Khalil (Journal of Tikrit University for Humanities, 2024)
This study deals with the task of revealing the patterns of opposite dualities represented by the love/hate dichotomy in the experience of the contemporary Iraqi poet Adeeb Kamal Al-Din as part of the process of revealing those artistic mechanisms that the poet uses in the manufacture of poetry of a contemporary artistic nature. The study attempts to show those links that his poetry relies on. The poet in the process of linking the contradiction, especially the love/hate dichotomy, he displays those aesthetic effects resulting from the employment of this opposing duality.